2020
DOI: 10.1161/jaha.119.015743
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes of Eggs and Cholesterol in Relation to All‐Cause and Heart Disease Mortality: A Prospective Cohort Study

Abstract: Background The aim of this study was to identify associations between dietary intakes of eggs and cholesterol and all‐cause and heart disease mortality in a US population. Methods and Results Data from the National Health and Nutrition Examination Survey 1999–2014 were used in this study, which included 37 121 participants ≥20 years of age. Dietary information was assessed via 24‐hour dietary recalls at baseline. Mortality status was documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Although most information on the nutritional risk factors CVD is derived (not clear) from the western reports, the prevalence of CVD is rapidly evolving towards epidemic proportions in the LEDCs with rapid changes in people’s lifestyle and food consumption behavior over the past few years [ 8 , 9 ] . However, a study in the USA did not find a significant association between dietary intake of eggs and all-cause and heart disease mortality among the US adults, whereas the total dietary cholesterol intake at high levels seemed to be associated with the higher risk of all-cause mortality [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most information on the nutritional risk factors CVD is derived (not clear) from the western reports, the prevalence of CVD is rapidly evolving towards epidemic proportions in the LEDCs with rapid changes in people’s lifestyle and food consumption behavior over the past few years [ 8 , 9 ] . However, a study in the USA did not find a significant association between dietary intake of eggs and all-cause and heart disease mortality among the US adults, whereas the total dietary cholesterol intake at high levels seemed to be associated with the higher risk of all-cause mortality [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiologic evidence regarding dietary cholesterol/eggs with health outcomes among non-White populations has been limited. To our knowledge, only two studies have examined the associations of cholesterol intake with cardiometabolic disease or all-cause mortality among Black Americans, including a subgroup analysis of 9204 Black Americans from a pooling project of six cohorts in the US and an analysis of 7683 Black Americans using the NHANES 1999–2014 data [ 12 , 30 ]. Consistent with our findings, both studies reported positive associations of cholesterol intake with all-cause mortality among Black Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, both studies reported positive associations of cholesterol intake with all-cause mortality among Black Americans. However, neither study, with small sample sizes, reported varied cholesterol–mortality associations across ethnicities [ 12 , 30 ]. Among White Americans, the null association between cholesterol and cardiometabolic mortality we observed was in line with the findings from two systematic reviews of 17 cohort studies [ 6 , 10 ], which included primarily white populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that we examined these differences in gene expression, as we identified upregulation not only in VAT, but also observed an increase of glutathione S-transferase mu 2 (Gstm2) expression in the PFC of rats fed WE-based diet. These are important considerations, as the data from clinical trials regarding WE consumption on inflammation-mediated cardiovascular disease are nuanced and remain contradictory ( 7 , 48 50 ). When specifically examining genes associated with disease we identified SPP1 which was down regulated 8.8-fold in VAT after consumption of the WE diet.…”
Section: Discussionmentioning
confidence: 99%